Study on the Rolling-Type Microvibration Isolation Mechanisms Based on Completely Elastic Contact. (25th February 2019) - Guan, Gaofeng; Xu, Dengfeng; Zhu, Yu; Yu, Qiang; Li, Qiang
Abstract : The previous models of rolling-type mechanisms were built based on rigid contact and pure rolling motion, but when applied to ground microvibration isolation, a large error in the natural frequency was sometimes observed in the experiments. A new model of a common mechanism based on completely elastic contact is developed, and the expression of the natural frequency is provided under a microvibration condition. The experiments and analysis show that the proposed model is more accurate than the previous model, and the natural frequency is independent of the payload. The analysis shows that the proposed model is only suitable in the range of completely elastic contact, and the load range is provided after comparing the experimental results with existing theory.